ChemInform Abstract: Catalytic Bio—Chemo and Bio—Bio Tandem Oxidation Reactions for Amide and Carboxylic Acid Synthesis. Issue 11 (March 2015) - Bechi, Beatrice; Herter, Susanne; McKenna, Shane; Riley, Christopher; Leimkuehler, Silke; Turner, Nicholas J.; Carnell, Andrew J.
Abstract Three water‐based one‐pot cascades to convert aryl alcohols to acids and amides, respectively, and cyclic amines to lactams are realized.